Analisis Komparatif Pengelolaan Sumber Belajar dan Implikasinya Terhadap Kualitas Pembelajaran Pada Dua Sekolah Dasar Islam Terpadu - Humaidah Fatimah Parapat; Misman (Institut Agama Islam Hidayatullah Batam, 2026)
This study aims to analyze the management of learning resources and its implications for the quality of learning in two Integrated Islamic Elementary Schools (SDIT), namely SDIT Al UMM Smart Center and SDIT Nurul Ilmi. This study uses a qualitative approach. The results show that both schools have a variety of learning resources available, including conventional, digital, and environmental learning resources. Differences in approaches to managing learning resources indicate significant differences in learning quality. The differences are seen in the level of optimization of learning resource utilization, especially digital media. SDIT Al UMM Smart Center tends to be more optimal in utilizing digital learning resources, resulting in increased enthusiasm, activeness, and collaboration skills of students compared to SDIT Nurul Ilmi, whose utilization is still not optimal. These findings indicate that learning quality is more influenced by the effectiveness of learning resource utilization than differences in management systems.